The state in a changing world the World Bank.. (Published for the World Bank, Oxford University Press, 1997)
"According to The World Bank the state is under attack. Its freedom in policy-making is being circumscribed by globalization and its dominion in the domestic arena is being challenged on many fronts. New technology and accumulated governmental failure have pulled the private sector into many areas which were considered the preserve of the state, and non-governmental organizations have intervened to deliver services better, faster, and cheaper than the state bureaucracy. Known as the standard reference for international economic data, the twentieth annual edition of the World Development Report focuses on the role of the state in a changing world. As in the past, a set of Selected World Development Indicators are provided as an appendix to the Report, presenting social and economic statistics for more than 200 countries. Moving well beyond basic economics, the Report deals with the challenging issue of political economy and institutional reform, moving from the what and why of reform to the when and how. The World Bank asserts that there is a rich record of state sector reform, but there are few tested rules. And because the structure of the state is also changing, issues of fiscal federalism have been brought to the forefront of the policy debate in the context of assertive regional and local authorities. The World Bank has worked on many of these issues and has accumulated a wealth of operational experience. It will now mobilize its resources to gain even more knowledge. The World Bank also plans to collaborate with several national and international agencies, building partnerships to address the tough practical questions of selectivity and implementation. The information in the Report will be used to explore on-going research from the Department of Economics at The World Bank, which examines issues of efficacy and efficiency in public expenditures and addresses the role of public management and the organization of civil service. Perhaps most important, the Report will have major implications for The World Bank and the donor community more generally as they collectively try to help countries find the right balance between public and private action and define the scope, modality, and organization of public management and responsibility." -- World Bank description.